STUDI LITERATUR TENTANG MOTIVASI BERPRESTASI SISWA REMAJA - Rusli Yana; Zulfan Saam; Elni Yakub (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This study aims to find out about the basic concepts of theory, know the factors that affect and how to increase the motivation of achievement of teenage students. The research method used is literature review. Strategies and steps used for literature study research are (1) Having general ideas on research topics, (2) Finding supporting information, (3) Emphasizing focus (expand/narrowing) and organizing reading materials, (4) Finding and finding reading materials, (5) Reorganizing materials and making research notes, (6) Reviewing and reorganizing reading materials, (7) Reorganizing reading materials and writing. The research object used is a teenage student. The results of this study show that the basic concepts of theory about motivation excel, among others: Grand theory by David McClelland, McGregor Theory, two-factor theory Frederick Herzberg, and McShane theory. Factors that influence motivation include: Self-Efficacy, Self-Efficacy, Self-concept, parental support, rewarding, student involvement, interpersonal communication, housing, school status, poverty, and tribal gaktor. Ways that can be done in improving the motivation of achievement include: the application of Symbolic Modeling techniques, Cooperative methods Type Student Teams Achievement Dividions (Stad), Teams Games, Solution- Focus Brief Group Counseling, guidance symbolic modeling technique group, use of cheerful cards, Handout activities, behavioral counseling Modeling Techniques, application of Peer Tutoring equipped with Macromedia Flash animation, providing positive Reinforcement, and Outbound activities.Key Words: Literature Studies, Motivation to Excel, Teen Students